2011
DOI: 10.1007/s12223-011-0008-2
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an arabinose-inducible system in Stenotrophomonas maltophilia

Abstract: A pBBad22T-derived conditioned arabinose (Ara)-inducible expression system was evaluated in Stenotrophomonas maltophilia (an opportunistic pathogen and has gained increasing attention as a cause of healthcare-associated infection). S. maltophilia cannot grow well when Ara is the sole available carbon source. The induction kinetic study, optimal inducer concentration determination, and depletion experiment were performed by using a xylE gene fusion construct, pBxylE, to monitor the expression of pBBad22T in S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Our system modulated dcas9 expression using different arabinose concentrations, and the highest level of dCas9 protein expression was observed at 0.2% (w/v) l -arabinose. These results are consistent with early studies showing that the araC repressor system had the ability to tightly control gene expression in the uninduced state and played an important role in regulating the production level over a wide range of dynamic concentrations. It is noteworthy that in S. maltophilia there may not be a pathway for arabinose degradation . We observed that AGS-1 fails to grow in minimal M9 medium when provided with only 0.2% l -arabinose as the exclusive carbon source (data not shown).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our system modulated dcas9 expression using different arabinose concentrations, and the highest level of dCas9 protein expression was observed at 0.2% (w/v) l -arabinose. These results are consistent with early studies showing that the araC repressor system had the ability to tightly control gene expression in the uninduced state and played an important role in regulating the production level over a wide range of dynamic concentrations. It is noteworthy that in S. maltophilia there may not be a pathway for arabinose degradation . We observed that AGS-1 fails to grow in minimal M9 medium when provided with only 0.2% l -arabinose as the exclusive carbon source (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…38−40 It is noteworthy that in S. maltophilia there may not be a pathway for arabinose degradation. 41 We observed that AGS-1 fails to grow in minimal M9 medium when provided with only 0.2% L-arabinose as the exclusive carbon source (data not shown). Furthermore, within the approximate range of below 0.2% L-arabinose concentration, there is no significant impact on the growth of S. maltophilia.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Therefore, a robust inducible expression system that can flexibly modulate the expression of target genes in Stenotrophomonas is urgently required. The arabinose-inducible araC -P BAD promoter from Escherichia coli would provide an alternative choice, exhibiting tighter control of gene expression, which is attributed to the dual roles of the regulatory protein AraC. , To date, the araC -P BAD system has been used for many bacteria, including E. coli , Pseudomonas , Xanthomonas , Corynebacterium , and Gluconobacter . ,, Although the evidence suggests that the araC -P BAD system is available to Stenotrophomonas KJ (a clinical isolate), the feasibility of this inducible expression system in Stenotrophomonas AGS-1 is still not clarified or confirmed. Thus it is necessary to design and construct an arabinose-inducible expression vector in Stenotrophomonas AGS-1.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 To date, the araC-P BAD system has been used for many bacteria, including E. coli, Pseudomonas, Xanthomonas, Corynebacterium, and Gluconobacter. 8,9,19−21 Although the evidence suggests that the araC-P BAD system is available to Stenotrophomonas KJ (a clinical isolate), 22 the feasibility of this inducible expression system in Stenotrophomonas AGS-1 is still not clarified or confirmed. Thus it is necessary to design and construct an arabinose-inducible expression vector in Stenotrophomonas AGS-1.…”
Section: ■ Introductionmentioning
confidence: 99%
“…AraC/P BAD regulatory system is an excellent inducible system and functions effectively in multiple species [33][34][35]. The original thermo-inducible sequences of kil were designed to be substituted by AraC/P BAD regulatory elements of E. coli (Fig.…”
Section: Construction and Functional Testing Of The Kil Counter-selection Cassettementioning
confidence: 99%